Application of COSMO-RS for pre-screening ionic liquids as thermodynamic gas hydrate inhibitor - Sulaimon, A.A. (Elsevier B.V., 2017)
Gas hydrate forms in oil and gas pipelines under low temperature and high pressure which result in flow assurance issues. To solve this, ionic liquids are introduced to act as dual inhibitors. Currently, the main method of studying the performances of ionic liquids is by conducting sometimes laborious experiments. Trial and error method as well as selection through literature are often employed in choosing the appropriate ionic liquids for gas hydrate inhibition. These methods are costly and probabilistic. In this work, Conductor-Like Screening Model for Real Solvents (COSMO-RS) software is used to pre-screen ionic liquids based on the fundamental property of the ionic liquid-hydrate system. The main energy that affects ionic liquid inhibition ability was found to be the hydrogen bonding energy (EHB). Results showed that increasing anion EHB improves inhibition ability while increasing cation EHB decreases the inhibition ability. Studies on the hydrogen bonding energies for double salt ionic liquids showed that the combination of chloride Cl− and hydrogen sulphate HSO4 as the anion has high hydrogen bonding energy. The introduction of the hydroxyl group OH− in the cation increased the hydrogen bonding energy between anion and water. The proposed ionic liquids for experimental tests are EMIMClHSO4, OH-EMIM Cl and OH-EMIMHSO4. © 2017 Elsevier B.V.